2000
DOI: 10.1002/1097-4555(200101)32:1<9::aid-jrs656>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of solid hydrogen sulfide: a lattice dynamics study

Abstract: A simple force constant model is described and applied to the vibrations of crystalline H2S and D2S in their low‐temperature ordered phase III, the structure of which has recently been determined. The model uses 14 adjustable parameters (three intramolecular and 11 intermolecular) to calculate the wavenumbers of 69 optical modes for each crystal, and good agreement with Raman and infrared data is obtained. The most important intermolecular interactions are confirmed to be hydrogen bonds, the formation of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…For crystalline phase III, using the peak values in Tables and , the average lattice rotational vibrations are at 175 and 130 cm -1 (frequency ratio = 1.35) for H 2 S and D 2 S, respectively, while the lattice translational vibrations are at 88 and 86 cm -1 (frequency ratio = 1.02) for H 2 S and D 2 S, respectively. These values for crystalline phase III are in close agreement with previous studies. , …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…For crystalline phase III, using the peak values in Tables and , the average lattice rotational vibrations are at 175 and 130 cm -1 (frequency ratio = 1.35) for H 2 S and D 2 S, respectively, while the lattice translational vibrations are at 88 and 86 cm -1 (frequency ratio = 1.02) for H 2 S and D 2 S, respectively. These values for crystalline phase III are in close agreement with previous studies. , …”
Section: Resultssupporting
confidence: 93%
“…5,6 This nonequivalence leads to splitting of some of the vibrations. 28,29 For these crystalline phase III spectra, the maximum peak positions for hydrogen sulfide are ν 2 at 1169, 1184, and 1189 cm -1 ; ν 1 at 2525 and 2536 cm -1 ; and ν 3 at 2548 cm -1 , while for deuterium sulfide they are ν 2 at 846, 856, and 860 cm -1 ; ν 1 at 1832 and 1840 cm -1 ; and ν 3 at 1852 cm -1 . These values give an average isotopic shift of 1.38.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was observed that the intensity of the E(TO 2 ) mode decreased with increasing temperature, and an abrupt intensity change in this mode occurred at 355 K due to the structural change from ferroelectric (tetragonal) to paraelectric (cubic). 15,48…”
Section: Structural Propertiesmentioning
confidence: 99%
“…A complete listing, together with references, may be found in our most recent paper on hydrogen sulfide. 2 By reproducing the wavenumbers of observed Raman and infrared peaks of these crystals, while using as few adjustable parameters as possible, the model allows important information about their principal intra-and intermolecular forces to be obtained. In this work, we applied the technique to the interesting layered crystal AsI 3 .…”
Section: Introductionmentioning
confidence: 99%